(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2006)
The new locality with dinosaur footprints has been discovered in the port of Karigador village in Istria. The site is situated in peritidal limestones of late Cenomanian age. The track-bearing horizon is bioclastic wackestone-packstone deposited in a subtidal environment. A single trackway which consist of 28 pairs of footprints and a group of 4 track pairs was registered at the site. Trackways belong to quadrupedal dinosaurs and are assigned to sauropods. Oval-circular shaped footprints represent the pedal prints and horseshoe-semicircular shaped ones represent the manus prints. The trackway is of narrow-gauge type with outwardly rotated manus and pedal prints. The average length of the pedal prints is 33 cm what indicates the length of the individual of app. 10 m. The preferred gait of the individual was a normal walk, taking normal strides with a speed of around 3 km/h. The trackmaker was a non-titanosaurian sauropod. Together with the other late Cenomanian sauropod localities in Istria (Fenoliga and Ladin Gaj), the Karigador site represents an example of sauropod tracks in a carbonate platform environment which can be assigned to Brontopodus ichnofacies.